Quantum dots for live cell imaging - Theresia Indahayu Kurniawan. (2011)
Quantum Dot (QD) has become the current most powerful technology for single molecule tracking. Its excellent ability to resist photobleaching, high signal to noise ratio, and large Stoke’s Shift are employed for live cell imaging. QD is attached to Adenosine 5’-triphosphate (ATP), a universal energy fuel for all living cells that also serves as communicator between cells. ATP has two different receptors on the cell surface, P2X and P2Y receptors. P2X works trough ion channel opening, allowing influx/efflux of Ca2+ for inducing short term effect such as signal transmission between neurons. P2Y is a G-protein coupled receptor (GPCR) which works through second messenger cascade system and is responsible for cell proliferation, neuronal differentiation, and programmed cell death. This project involves study of ATP receptor behaviour inside the living PC12 (pheochromocytoma 12) cell during its differentiation state which was induced by neutrophin Neural Growth Factor (NGF) and during its apoptotic state which was done by removing glucose from medium environment (hypoglycemic) with Total Internal Reflection Fluorescence Microscopy (TIRFM) for imaging.